2021
DOI: 10.3390/children8020111
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Children in Greece and Its Relationship with Sunscreen Application

Abstract: The aim of this study was to characterize the prevalence and seasonal variation of vitamin D (vit D) deficiency/insufficiency in healthy children and adolescents in Greece, and to explore its relationship with the use of sunscreens. The serum level of 25-hydroxy-vitamin D (25(OH)D) was measured in 376 children and adolescents (184 males and 192 females) with a mean age of 7.6 ± 4.9 years, at different time points over a period of 13 months. The prevalence of low serum 25(OH)D level, including deficiency and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
5
9
2
1
Order By: Relevance
“…The incidence of atopic manifestations is typically higher among boys [7], and our results are in accordance with this gender difference. As in other studies [30], our study showed an inverse relationship between 25(OH)D level and age in healthy children and adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of atopic manifestations is typically higher among boys [7], and our results are in accordance with this gender difference. As in other studies [30], our study showed an inverse relationship between 25(OH)D level and age in healthy children and adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…Other sources of vitamin D3 (cholecalciferol) are animal foods and vitamin D3 supplements, while vitamin D2 (ergocalciferol) is derived from the intake of vegetable foods and vitamin D2 supplementation [ 50 ]. As exposure to the sun varies according to the season, time of day, latitude, altitude, skin pigmentation and other conditions, food sources are required to cover the required 15 μg daily intake set by the European Food Safety Authority (EFSA) [ 51 , 52 ]. Good sources of dietary vitamin D2 are oily fish and fish liver oils, mushrooms, reindeer lichen ( Cladonia rangiferina ), beef liver, eggs, dark chocolate and cheese.…”
Section: Vitamin D: Sourcesmentioning
confidence: 99%
“…9,17 These data also showed that VD status in early childhood was not affected by gender and was similar to that of Greek counterparts. 37 Vitamin D status in late-stage children and adolescents was influenced by gender, which differed from the findings of European and Greek counterparts. 9,37 These differences in VD status are thought to be related to supplemental VD intake and lifestyle (outdoor activities).…”
Section: The Status Of Vd Deficiency Insufficiency Adequacy or Excess...mentioning
confidence: 73%